2017
DOI: 10.1007/s13365-017-0557-5
|View full text |Cite
|
Sign up to set email alerts
|

Effort and neuropsychological performance in HIV-infected individuals on stable combination antiretroviral therapy

Abstract: The expression of cognitive symptoms associated with HIV varies over time and across individuals. This pattern may reflect transient contextual factors, including the degree of effort exerted by individuals undergoing cognitive testing. The present study examined whether effort corresponds to the expression of persistent HIV-related cognitive impairment among individuals receiving combination antiretroviral therapy (cART). HIV+ individuals (n = 111) averaged 48.2 (14.9) years of age 13.0 (2.7) years of educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…49 Two studies reported validity results in people with HIV-in one study 15% of 111 people with HIV (stable on antiretroviral therapy) failed trial 1 of the TOMM (note, TOMM is usually scored on trial 2 or a delayed trial); and in another 17% of 30 failed the Amsterdam Short-Term Memory Test. 50 51 A study of neuropsychological performance in adults with sickle cell disease reported low failure rates on the TOMM and on RDS ≤6, but 33% of 43 failed RDS with a ≤7 cut-off. 52 candidates with essential tremor failed the WMT.…”
Section: Other Conditionsmentioning
confidence: 99%
“…49 Two studies reported validity results in people with HIV-in one study 15% of 111 people with HIV (stable on antiretroviral therapy) failed trial 1 of the TOMM (note, TOMM is usually scored on trial 2 or a delayed trial); and in another 17% of 30 failed the Amsterdam Short-Term Memory Test. 50 51 A study of neuropsychological performance in adults with sickle cell disease reported low failure rates on the TOMM and on RDS ≤6, but 33% of 43 failed RDS with a ≤7 cut-off. 52 candidates with essential tremor failed the WMT.…”
Section: Other Conditionsmentioning
confidence: 99%
“…No participant in our sample met the Cogstate manual recommendations for questionable data integrity; however, we are not aware of any similar data checks for the NIH Toolbox and neither measure has validated embedded PVTs for HIV disease. Although prior studies support low base rates of PVT failures in participants with HIV (Paul et al, 2017;Woods et al, 2003), the validity of neuropsychological performance is an important component of neuropsychological assessment (Lippa, 2018). A fifth limitation is that we do not know the frequency of PM impairment in this sample, as there are no U.S. normative standards for the CAMPROMPT and the available U.K. norms are not adequately representative of the diverse older PWH in this study to warrant their application.…”
Section: Discussionmentioning
confidence: 87%
“…Raw test scores were converted into demographically adjusted (age, sex, race, and education) standardized z scores using appropriate normative standards (see Table, Supplemental Digital Content 1, http:// links.lww.com/QAI/B783, which summarizes results of individual cognitive tests). 27,28 The Z scores were averaged to create domain Z scores. The 4 domain Z scores were then averaged to create an overall cognition Z score.…”
Section: Neuropsychological Performance Measurementmentioning
confidence: 99%